2014
DOI: 10.1007/s11547-014-0429-5
|View full text |Cite|
|
Sign up to set email alerts
|

C-arm cone-beam computed tomography in interventional oncology: technical aspects and clinical applications

Abstract: C-arm cone-beam computed tomography (CBCT) is a new imaging technology integrated in modern angiographic systems. Due to its ability to obtain cross-sectional imaging and the possibility to use dedicated planning and navigation software, it provides an informed platform for interventional oncology procedures. In this paper, we highlight the technical aspects and clinical applications of CBCT imaging and navigation in the most common loco-regional oncological treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 65 publications
(63 reference statements)
1
58
0
Order By: Relevance
“…However, unlike in DSA, in cone-beam CT, the skin dose of radiation is distributed over 180° of the body being imaged because of the rotational nature of the acquisition (17,18). Moreover, a single cone-beam CT examination can yield the same information as multiple DSA acquisitions in technically challenging cases, and may, therefore, reduce the total amount of radiation exposure, procedural time, and contrast medium use (19,21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, unlike in DSA, in cone-beam CT, the skin dose of radiation is distributed over 180° of the body being imaged because of the rotational nature of the acquisition (17,18). Moreover, a single cone-beam CT examination can yield the same information as multiple DSA acquisitions in technically challenging cases, and may, therefore, reduce the total amount of radiation exposure, procedural time, and contrast medium use (19,21).…”
Section: Discussionmentioning
confidence: 99%
“…Authors of several studies (16)(17)(18)(19) have shown that the use of cone-beam CT could be extremely helpful during transcatheter arterial chemoembolization, especially in cases of complex hepatic arterial anatomy. However, to our knowledge, studies of the use of cone-beam CT to evaluate the PA anatomy are limited (15,20,21 …”
Section: Study Populationmentioning
confidence: 99%
“…This imaging technique provides cross sectional, soft-tissue, CT-like images without the need to move the patient to a CT room and offers many advantages over classic 2D angiography alone 15 , 17 , 19 , 32 . First, CBCT detection accuracy of HCC lesions is equivalent to multidetector CT and MRI and superior to 2D angiography 15 , 17 , 19 . Second, it is the most accurate imaging technique to identify tumor-feeding arteries 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Cone-beam CT (CBCT) is a novel technique that is increasingly used during TACE for inoperable HCC 15 - 20 . This imaging technique uses a flat-panel detector angiographic system to produce CT-like soft-tissue images without the need to transfer the patient to a CT unit 15 , 17 , 19 . It can be used to visualize tumor-feeding vessels and parenchymal stain during TACE, achieving detection accuracies significantly superior to standard 2D angiography 17 …”
Section: Introductionmentioning
confidence: 99%
“…In this context, MIP, MPR and SSD images reconstruction (Figs. 4 and 5) are an indispensable tool which allows multidetecor CTA to provide specific and precise measurements of anterograde or retrograde extent of dissection, including length, diameter of the aorta and the true and false lumens, involvement of vital vasculature, and distance from the intimal tear to the vital vascular branches [3,7,35].…”
Section: Classification Of Endoleaksmentioning
confidence: 99%